Data of the quantification of the influence of DMSO concentration on the kinetic of interaction between TNFα and SPD304 - Ghada Attia (Elsevier, 2021)
The data presented here are related to the article entitled “New contributions to the drug profile of TNFα inhibitor SPD304: affinity, selectivity ADMET considerations” published in the European Journal of pharmacology. As DMSO is usually used as a co-solvent to dissolve low aqueous soluble small molecules, such as SPD304, we have investigated the influence of its concentration on the kinetic of interaction between tumor necrosis factor α (TNF-α) and its inhibitor, SPD304. The presented data, acquired using a surface acoustic wave sensor, can be used in further biological studies to compare the kinetic of interaction between proteins/small molecules in general and TNFα/inhibitors in particular. The estimated dissociation constant can be compared to other ones to statute on the degree of affinity between a protein and a given molecule.